2017
DOI: 10.14326/abe.6.21
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of External Forces on the Basis of Local Displacement Observations of an Elastic Body

Abstract: Surgery can become safer and more reliable if the conditions of the organs can be physically and quantitatively assessed through simultaneous intraoperative measurements and physical estimations of deformed organs. This study proposes a new method for estimating external forces based on local displacement of elastic bodies. Using this method, one can estimate the magnitude and position of forces not only on the forceps but also in the invisible eld. Simulation studies con rmed the effectiveness of this method.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, application of the model-based approach has been restricted because the entire shape of organs cannot be obtained in many clinical situations such as ultrasound and intraoperative imaging. Recent study reports external force can be estimated using locally observed displacements of the deformed state [7]. To the best of our knowledge, without our preliminary study [5], no report has appeared investigating elasticity reconstruction that includes unobservable areas of elastic bodies.…”
Section: Introductionmentioning
confidence: 93%
“…However, application of the model-based approach has been restricted because the entire shape of organs cannot be obtained in many clinical situations such as ultrasound and intraoperative imaging. Recent study reports external force can be estimated using locally observed displacements of the deformed state [7]. To the best of our knowledge, without our preliminary study [5], no report has appeared investigating elasticity reconstruction that includes unobservable areas of elastic bodies.…”
Section: Introductionmentioning
confidence: 93%
“…In order to estimate the shape of the elastic object, matching algorithms based on shape descriptors [24], a method using weighted patch iterative closest point of the mesh [25], and a method using laser range scanner data to obtain information about the surface of the moving tissue [26] have been proposed. In another study, the external force applied to an object was estimated using partial observation, to overcome limited visibility at the time of surgical treatment [27]. In their work, it is necessary to assume that the properties related to the shape of the object are invariant before and after the deformation.…”
Section: Related Workmentioning
confidence: 99%
“…The models used in medical virtual reality organ simulators [8,9] require information about the elasticity of biological tissues. If such data could be obtained during surgery without additional hardware or time/cost burdens, various areas of biomed-ical research and intraoperative support systems [10,11] would bene t.…”
Section: Introductionmentioning
confidence: 99%